PENGARUH NILAI KURS, INFLASI, DAN PDB TERHADAP EKSPOR TEMBAGA DI INDONESIA - Rendy Alvaro (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
In the 2015-2019 National Medium-Term Development Plan, the direction of policies and strategies for developing national trade capacity are carried out through two pillars of policy direction, namely the development of domestic trade and the development of foreign trade. Due to sluggish global conditions Indonesia’s export declines significantly. This study aims to analyze the effects of Exchange Rate, Inflation and Gross Domestic Product on copper exports in Indonesia. Method to analyse effects of Exchange Rate, Inflation and Gross Domestic Product on Copper Exports in Indonesia is by using multiple regression analysis. The results of the study show that the exchange rate, inflation and GDP together have a significant effect on Indonesia's copper exports.